Phenotypic identity of gastric mucous neck cells and mucous cells of cardiac, pyloric, and Brunner's glands. - Hughes, N R (1994)
AIM--To investigate the tissue specificity of a novel monoclonal antibody raised to a tissue fraction of normal human liver and which identified certain cells of gastric and duodenal mucosa. METHODS--A total of 155 samples of various tissues obtained from 100 surgical specimens were fixed in cold ethanol-paraformaldehyde, embedded in paraffin wax, and 3 microns sections were studied by immunohistochemical and lectin staining procedures. RESULTS--Immunohistochemical staining showed a major tissue specific component which was strongly expressed by mucous neck cells of the body of the stomach, glands of the cardia and pyloric antrum, and by Brunner's glands. Staining for antigen in the periductal glands of normal major biliary and pancreatic ducts was variable and relatively weaker. It was not detected elsewhere in normal intestine or in the other normal tissues tested. Barrett's mucosa of gastric cardia type, and pyloric gland metaplasia in the gall bladder and small bowel affected with Crohn's disease stained for the antigen. The tissue distribution of the antigen was identical with that of a glycoprotein, demonstrated by an induced affinity for concanavalin A following treatment of tissue sections with periodic acid. The antigen was not sensitive to sialidase. CONCLUSIONS--The tissue component identified (designated here as antigen D10) seems to be characteristic of certain differentiated epithelial cells derived from that part of foregut giving rise to stomach, duodenum, and biliary and pancreatic ducts. The antibody will be of use in investigating pathological processes involving tissue differentiation at these sites, and in the oesophagus and intestines.